Sagot :
✒️[tex]\large{\mathcal{ANSWER}}[/tex]
[tex]======================[/tex]
- The ordered pair that makes the system of equations is; (4, -1).
Let's solve the system of equations using the method of elimination.
[tex]2x + 7y = 1 \\ - 2x + 3y = - 11[/tex]
[tex]------------------[/tex]
Let's join the two equations, add the second equation to the first.
[tex]2x + 7y - 2x + 3y = 1 - 11[/tex]
2x and -2x are opposites, since the sum of opposites is equal to zero, let's take them out of the equation.
[tex]7y + 3y = 1 - 11[/tex]
Calculate the first and second numbers of the equation.
[tex]10y = - 1[/tex]
Pass the number that is multiplying the unknown to the second dividing member.
[tex]y = \frac{ - 10}{10} [/tex]
[tex] \: \boxed{y = -1} [/tex]
[tex]======================[/tex]
We have the value of y is -1, substitute the given value in one of the equations to find the value of x. I'm going to choose the equation 2x + 7y = 1 as it's the simplest equation.
[tex]2x + 7 \times ( - 1) = 1[/tex]
Solve the Multiplication;
[tex]2x - 7 = 1[/tex]
Pass the number -7 to the second member, change his sign.
[tex]2x = 1 + 7[/tex]
Solve the second number;
[tex]2x = 8[/tex]
Pass the number that is multiplying the unknown to the other side by dividing.
[tex]x = \frac{8}{2} [/tex]
[tex] \: \boxed{x = 4} [/tex]
[tex]======================[/tex]